Nitrogen-concentration modulated interface quality, band alignment and electrical properties of HfTiON/Ge gate stack pretreated by trimethylaluminum precursor. (July 2017) - Gao, J.; He, G.; Xiao, D.Q.; Jiang, S.S.; Lv, J.G.; Cheng, C.; Sun, Z.Q.
Graphical abstract: Highlights: Sputtering-derived HfTiON gate dielectrics have been deposited on Ge substrates. Nitrogen incorporation suppress the formation of GeO2 and germanate at the interface. N should be carefully controlled to meet the best performance requirement for Ge-based CMOS device. Abstract: Effects of nitrogen incorporation on the interface chemical bonding states, band alignment and electrical properties of sputtering-derived HfTiO high-k gate stacks on Ge substrates pretreated by trimethylaluminum (TMA) precursor have been investigated by X-ray photoemission spectroscopy (XPS), UV–vis transmission spectroscopy, and electrical measurements. XPS results indicate that incorporation of a moderate amount of nitrogen (3 sccm) incorporation can effectively suppress the formation of unstable GeO2 and low-k germinate at the interfacial region. Meanwhile, reduction in band gap and valence band offset and increase in conduction band offset have been observed after nitrogen incorporation. Electrical properties were evaluated by capacitance-voltage ( C–V ) and leakage current density-voltage ( J–V ) measurements based on MOS capacitors. Small gate leakage current (4.13 × 10 −7  A/cm 2 at Vg  = 1 V), almost disappeared hysteresis, and large dielectric constant (19.6) that have been observed for MOS capacitor with HfTiON/Ge stacked gate dielectric with N2 flow of 3 sccm.